VARIATIONS IN THE EARTH'S GRAVITY FIELD CAUSED BY TORSIONAL OSCILLATIONS IN THE CORE - Dumberry M.; Bloxham J. (My University, 2004)
We investigate whether a component of the flow in the Earth's fluid core, namely torsional oscillations, could be detected in gravity field data at the surface and whether it could explain some of the observed time variations in the elliptical part of the gravity field (J2). Torsional oscillations are azimuthal oscillations of rigid coaxial cylindrical surfaces and have typical periods of decades. This type of fluid motion supports geostrophic pressure gradients, which produce deformations of the core–mantle boundary. Because of the density discontinuity between the core and the mantle, such deformations produce changes in the gravity field that, because of the flow geometry, are both axisymmetric and symmetric about the equator. Torsional oscillations are thus expected to produce time variations in the zonal harmonics of even degree in the gravity field. Similarly, the changes in the rotation rates of the mantle and inner core that occur to balance the change in angular momentum carried by the torsional oscillations also produce zonal variations in gravity. We have built a model to calculate the changes in the gravity field and in the rotation rates of the mantle and inner core produced by torsional oscillations. We show that the changes in the rotation rate of the inner core produce changes in J2 that are a few orders of magnitude too small to be observed. The amplitudes of the changes in J2 from torsional oscillations are 10 times smaller than the temporal changes that are observed to occur about a linear secular trend. However, provided the mechanism responsible for these changes in J2 is identified and that this contribution is removed from the data, it may be possible in the future to detect the lowest harmonic degrees of the torsional oscillations in the gravity field data. We also show that torsional oscillations have contributed to the linear secular change in J2 by about −0.75 × 10−12 per year in the last 20 years. Finally, the associated change in the vertical ground motion at the surface of the Earth that is predicted by our mechanism is of the order of 0.2 mm, which is too small to be detected with the current precision in measurements.
Keywords: core–mantle boundary; Earth’s core; Earth’s rotation; figure of Earth; gravity field; torsional oscillations